Satisfaction of the Patients about the Health Services Provided in the Primary Health Care Centers in Riyadh City - AlShehri, Hatem (The Arab Journal of Administration, 2021)
The research aims to highlight the satisfaction of the Patients about the health services provided in the primary health care centers in Riyadh city in terms of features, services and location of the centers in addition to the health service provided, staff and electronic services. As the research community was the primary health care centers in Riyadh, the study consisted of 200 random sample references from four different locations according to the appropriate geographic distribution. The samples were collected according to the distribution of random electronic questionnaires to the visitors of these centers. In order to achieve the objectives of this research was used descriptive analytical method, which is by describing the extent of satisfaction and analysis and knowledge of the components of the characteristics of the Patients center. The researcher reached a number of results, the most important of which is the majority of the Patients of the centers in the category of women, in addition to the lack of availability of medicines, lack of electronic services and the appropriate construction in providing the service with high quality, and in the development and training of the employees. Based on the findings of the researcher, he recommended the importance of developing government buildings in addition to raising the efficiency of the workforce and training them, and working to provide the shortage of special medicines and other support services such as radiology and the development of electronic services and their unification and linking them in an integrated way serves the unified electronic record and contributes to its application.